Current Account Balances, Financial Development and Institutions: Assaying the World Savings Glut - Chinn, Menzie D.; Ito, Hiro (My University, 2006)
Through investigation of the medium-term determinants of the current account the authors find that for industrial countries, the government budget balance is an important determinant of the current account balance. However, their empirical findings are not consistent with the argument that the more developed financial markets are, the less saving a country undertakes. There is no evidence of excess domestic saving in the Asian emerging market countries; rather they seem to have suffered from depressed investment in the wake of the 1997 financial crises. The authors find that the more developed equity markets are, the more likely countries are to run current account deficits.